2015
DOI: 10.1093/ckj/sfv073
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor 23 and parathyroid hormone predict extent of aortic valve calcifications in patients with mild to moderate chronic kidney disease

Abstract: BackgroundCardiac valve calcifications are present in dialysis patients and regarded as dependent on a deranged mineral metabolism. Few data are available for patients with chronic kidney disease (CKD) not on dialysis. This study evaluates the potential association between the extent of cardiac valve calcification and levels of intact parathyroid hormone (i-PTH), phosphorus, calcium, 25-OH vitamin D, fibroblast growth factor 23 (FGF-23), Klotho and C-reactive protein (CRP) simultaneously measured in patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 37 publications
2
27
0
Order By: Relevance
“…In this situation, the FGF23-mediated increase in renal-tubular calcium reabsorption may contribute to calcium retention and vascular calcification. The recently reported positive association between aortic valve calcification and serum FGF23 as well as serum PTH in patients with CKD supports this line or argumentation [76].…”
Section: Distal Tubular Calcium and Sodium Transportmentioning
confidence: 57%
“…In this situation, the FGF23-mediated increase in renal-tubular calcium reabsorption may contribute to calcium retention and vascular calcification. The recently reported positive association between aortic valve calcification and serum FGF23 as well as serum PTH in patients with CKD supports this line or argumentation [76].…”
Section: Distal Tubular Calcium and Sodium Transportmentioning
confidence: 57%
“…A large study including 6,814 people without cardiovascular disease demonstrated that higher serum phosphate levels were associated with a significantly greater prevalence of aortic valve calcification, without significant correlations of aortic valve calcification with serum FGF23 and iPTH levels or urinary phosphate excretion [30]. Another research reported that aortic valve calcification was significantly correlated with serum FGF23 and iPTH levels, but not with serum calcium, phosphate, or 25-hydroxyvitamin D levels in patients with mild to moderate CKD [31].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, aortic valve calcification score of patients is negatively correlated with circulating Klotho levels [41]. The Klotho −/− mouse model, which exhibits premature aging associated with hyperphosphatemia and low vitamin D, has been used to study age-related diseases, including CKD and vascular calcification.…”
Section: Discussionmentioning
confidence: 99%